La catedral gótica de León. El inicio de la construcción a la luz de nuevos datos y reflexiones sobre la escultura monumental - Herráez Ortega, María Victoria (Estudios humanísticos. Geografía, historia y arte, 2001)
The monumental sculpture of León's Cathedral has been traditionally dated in accordance with the cronology attributed to the building. The documents which have been recently dealt with from the Cathedral's archive have elicited a new dating, bringing forward the time of the the sculptors' work. This fact allows us to state the beginning of the Gothic construction in the first half of the 13'h century, probably before the death of bishop Martín Rodríguez (d. 1242).